Does the EMU Need a Fiscal Transfer Mechanism? - Davide Furceri (Vierteljahrshefte zur Wirtschaftsforschung, 2004)
The aim of this paper is to investigate how the birth of a central fiscal authority or the creation of a fiscal transfer mechanism could improve the action of fiscal policy in terms of stabilization in the EMU. In particular, the paper examines the theoretical reasons to support this conclusion and provides empirical evidence that shows how the EMU is not able to face asymmetric and symmetric idiosyncratic shocks. – – Die zentrale Frage des Aufsatzes lautet: Ob und wie kann eine zentrale Fiskalbehörde oder ein fiskalischer Transfermechanismus die fiskalpolitische Stabilisierung in der EWU verbessern? Dazu werden theoretische Argumente und empirische Evidenz präsentiert, die die These bestätigen, dass die gegenwärtige EWU nicht in der Lage ist, asymmetrische und symmetrische idiosynkratische Schocks zu verarbeiten.
Keywords: 330; Finanzpolitik; Eurozone; Schock; EU-Staaten; Europäischer Stabilitätsmechanismus